Evaluation of My Medication Passport: a patient-completed aide-memoire designed by patients, for patients, to help towards medicines optimisation. Issue 8 (19th August 2014) - Barber, Susan; Thakkar, Kandarp; Marvin, Vanessa; Franklin, Bryony Dean; Bell, Derek
Abstract : Objectives: A passport-sized booklet, designed by patients for patients to record details about their medicines, has been developed as part of a wider project focusing on improving prescribing in the elderly ('ImPE'). We undertook an evaluation of 'My Medication Passport' to gain an understanding of its value to patients and how it may be used in communications about medicines. Setting: The Passport was launched in secondary care with the initial users being older people discharged home after an admission to one of the four North West London participating Trusts. The uptake subsequently spread to other (community) locations and other age groups. Participants: We recruited more than 200 patients from a cohort who had been given a passport as part of the improvement projects at one of four sites. Of them, 63% (133) completed the structured telephone questionnaire including 27% for whom English was not their first language. Approximately half of the respondents were male and 40% were over 70 years of age. Results: More than half of the respondents had found their medication passport useful or helpful in some way; 42% through sharing details from it with others (most frequently family, carer or doctor) or using it as a platform for conversations with healthcare professionals. One-third of those questioned carried the passport with them at all times. Conclusions: My Medication Passport has been positively evaluated; we have a better understanding of how it is used by patients, what they are recording and how it can be an aid to dialogue about medicines with family, carers and healthcare professionals. Further development and spread is underway including an App for smartphones that will be subject to wider evaluation to include feedback from clinicians.